2013
DOI: 10.1051/matecconf/20130301008
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic assessments of the Fe-Y and Ni-Sc systems

Abstract: Abstract. The present study concerns the optimization of the Fe-Y and Ni-Sc systems by the help of the CALPHAD (CALculation of Phase Diagram) method, taking into account the available experimental results about phase equilibria and thermodynamic properties. The excess terms of the Gibbs energy of the solution phases (liquid, b.c.c., f.c.c. and h.c.p.) were assessed with the recent exponential temperature dependence of the interaction energies by Kaptay and compared with the linear dependence by Redlich-Kister… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…[100] The calculated Gibbs energy data from the present study is slightly lower than the experimental values. But the previous assessments [90][91][92]107] show a much larger deviation from the experimental data. The enthalpy of formation data also shows similar results.…”
Section: The Fe-y (Iron-yttrium) Systemmentioning
confidence: 64%
See 3 more Smart Citations
“…[100] The calculated Gibbs energy data from the present study is slightly lower than the experimental values. But the previous assessments [90][91][92]107] show a much larger deviation from the experimental data. The enthalpy of formation data also shows similar results.…”
Section: The Fe-y (Iron-yttrium) Systemmentioning
confidence: 64%
“…The phase diagram depicted is identical to that assessed from the present study, except no terminal solid solutions were considered. Kardellass et al [92,107] presented a phase diagram with considerable homogeneity range in the Y 6 Fe 23 and YFe 2 phase without any experimental evidence. Several investigators [108,109] reported the presence of a stoichiometric phase, without any solid solubility of Fe in Y 6 Fe 23 .…”
Section: The Fe-y (Iron-yttrium) Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…To clarify this question, we need to survey a number of binary systems of scandium with metals, which show relatively similar degrees of interaction between the components to the Co-Sc system [10,38,[41][42][43][44][45][46][47][48][49][50][51][52][53].…”
Section: Discussionmentioning
confidence: 99%